1961
DOI: 10.1042/bj0810596
|View full text |Cite
|
Sign up to set email alerts
|

Studies on human urinary and pituitary gonadotrophins

Abstract: 2. Deacetylcephalosporin C has been isolated as a crystalline sodium salt. It resembles cephalosporin C in a number of its properties, including its ultraviolet-absorption spectrum, but is more readily converted into the lactone, cephalosporin Cc, in acid solution. 3. Deacetylcephalosporin C shows about 20 % of the activity of cephalosporin C against Staphylo-coccu8 aureu?s (Oxford strain) and Salmonella typhi. It is highly resistant to hydrolysis by purified preparations of penicillinase from Bacillus cereus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

1967
1967
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(38 citation statements)
references
References 7 publications
1
36
0
1
Order By: Relevance
“…From a second group of six laparotomized hens, three were (Butt et al, 1961;Kirkham, 1962). The ovary and oviduct development observed here confirmed that the material had gonad-stimulating properties.…”
Section: Pituitary-deficient Henssupporting
confidence: 62%
See 1 more Smart Citation
“…From a second group of six laparotomized hens, three were (Butt et al, 1961;Kirkham, 1962). The ovary and oviduct development observed here confirmed that the material had gonad-stimulating properties.…”
Section: Pituitary-deficient Henssupporting
confidence: 62%
“…Acetone-dried broiler pituitary glands were powdered, yielding 1 -2 mg/gland (Wright, 1965 (Butt, Crooke & Cunningham, 1961) and yielded 4-2% precipitate (by weight) of the initial powder (Hartree, unpublished data), equivalent to 0-045 mg/gland.…”
Section: Chicken Pituitary Gonadotrophin (Cpg)mentioning
confidence: 99%
“…Human pituitary FSH was extracted and assayed as described by Butt, Crooke & Cunningham (1961). In Exps 1 and 2 and in two replicates of Exp.…”
Section: Gonadotrophinsmentioning
confidence: 99%
“…The excretion of oestriol was below normal more than 2 weeks before the abortion occurred in No. 1,676 and 1,835 (1), and the excretion of all 3 hormones significantly decreased at that time in No. 1,835 (1).…”
Section: Resultsmentioning
confidence: 99%
“…[5] and expressed as mg/24 h, and chorionic gonadotrophin by the haemagglutination method of Burr et at. [1] and expressed as IU/24h. Altogether, there were 1,277 estimations of oestriol, 1,219 of pregnanediol and 933 of chorionic gonadotrophin.…”
Section: Methodsmentioning
confidence: 99%